Patch Testing as a Corroborative and Diagnostic Tool in Patients Suspected of Contact Allergen Induced Facial Melanosis - Vedant M Ghuse; Shylaja Someshwar (Wolters Kluwer Medknow Publications, 2021)
Background: Hypermelanosis involving predominantly the face and neck is relatively common and often presents a complex diagnostic problem. Objective: To study the patterns of facial melanosis in Indian skin and assess the importance of patch testing as a corroborative tool in the diagnosis of facial melanosis. Subjects and Methods: A total of 50 patients who consented to the study and satisfied the inclusion and exclusion criteria were incorporated in the study. These patients were subjected to a detailed history, clinical, dermoscopic, and histopathological evaluation. Patch testing using the universal series, cosmetic series, and photopatch was done on those who satisfied the inclusion criteria. Suspected allergen "as is" patch testing was done in selected cases. Results: Facial melanosis as a result of contact dermatitis is a common entity and was seen in the age group of 18-70 years in both the sexes with male to female ratio of 6.5:2.5 indicating a male preponderance. The most common dermoscopic finding was the presence of reticular pigment network seen in 33 (66%) cases. Histopathology showed increased basal melanin in 56% and pigment incontinence in 26% of the cases. The commonest allergen in men was found to be potassium dichromate (15%), while in females it was nickel (20%). Photopatch test was done for all the patients and was positive in five cases (10%). Suspected allergen "as is" patch testing was negative in all the cases. Conclusions: Facial melanosis as a result of contact dermatitis can be confused with other acquired dermatological conditions causing hyperpigmentation. Therefore, a detailed history of contact with allergens has to be elicited, and if found relevant, has to be confirmed by patch testing.